Negara Hukum Indonesia: Dekolonisasi dan Rekonstruksi Tradisi - Aidul Fitriciada Azhari (Jurnal Hukum IUS QUIA IUSTUM, 2012)
The research will examine the discourse of Pancasila-based constitutional state and the relevance in Indonesia’s life after the amendments to the 1945 Constitution of Indonesia. The research uses a normative legal approach combined with a material-based analysis. The result shows that the founding fathers accepted the concept of Rechtsstaat, but they changed the basis of social-economy from liberal economic system into planned economic system. The change was made by expediting the process of social-economy decolonization and tradition reconstruction; as a result, the constitutional state of Indonesia exists on the basis of welfare state and Indonesian legal traditions. The aims are not only to ensure legal certainty for economic business but also to provide justice and welfare for all citizens. Although it was unclearly stated that the amendments to the 1945 Constitution of Indonesia rejected the free trade economic system, it has eliminated GBHN as the instrument to implement the planned economic system as regulated in Article 33 Verse (1) of the 1945 Constitution of Indonesia. Consequently, the economic system tends to move towards the free trade system, which is parallel to the concept of liberal-constitutional state and principally against the values of Pancasila that aim to grant social justice for all Indonesian citizens.